Knowing me, knowing you: What’s the matter with s 21(1)(B) of the Insurance Contracts Act 1984 (Cth)? - Allison, Simon (LexisNexis, 2023)
The objective test of non-disclosure in s 21(1)(b) of the Insurance Contracts Act 1984 (Cth) remains elusive in its meaning and operation. Despite the time of assessment being prior to entry into a contract of insurance, disputes over an insured’s non-disclosure inevitably arise after a claim is made, when investigations uncover matters an insurer argues were relevant to its decision to accept the risk of a contract of insurance, and the circumstances on which it does. The test in s 21(1)(b) did away with the common law prudent insurer standard of materiality. Despite this, resolution of questions of non-disclosure can be complex exercises in inference drawing, and courts are reticent to give weight to hindsight evidence of insurers. Complex fact scenarios involving the disclosure of opinions and allegations cases have put into question the practical utility of settled principles on the application of the test. Recent cases demonstrate a move towards a broader consideration of circumstances relevant to s 21(1)(b), providing a more flexible construction to resolve conceptual issues that the legislation is otherwise silent on.